The Relationship Between Family Support and the Application of Parenting Patterns - Ina Agustina; B. Kedang Sabinus; Yulianti Kristiani Banhae (GLOBAL HEALTH SCIENCE GROUP, 2022)
Good parenting patterns receive less attention from the community, especially farming communities with low economic levels, education levels and insight into the growth and development of children. From preliminary data, there are some parents in Kuanheun village who say